Effects of ZnO nanoparticles concentration on the morphology and textural properties of ZnO/NiFe2O4 nanocomposite - Jimoh Oladejo Tijani; Augustine Innalegwu Daniel; Sarah Udenyi Onogwu; Ambali Saka Abdulkareem; Usman Ahmed Aminu; Marshall Keyster; Ashwil Klein (MethodsX)
The aim of this study is to synthesize and characterize ZnO and NiFe2O4 nanoparticles via green route and co-precipitation of ZnO/NiFe2O4. X-ray diffraction (XRD) data show no extra diffraction peaks belonging to other phases except wurtzite. High resolution transmission electron microscopy (HRTEM) images showed that the average interplanar distance of wurtzite phase at 3, 5, and 7 % dopant concentration were about 0.28, 0.44 and 0.33 nm respectively. X-ray photoelectron spectroscopy (XPS) results show difference in binding energies of the elements present in different concentration of the dopants. Electron Energy Loss Spectroscopy (EELS) spectra show similarities in the shape of Zn, Fe and Ni from zero loss, low loss and core loss region with a little shift in energy. All the elements exhibit multiple oxidation state; +2 and +3 for Fe and +1 and +2 for Zn and Ni. Brunauer-Emmett-Teller (BET) plot shows that ZnO belongs to the type II isotherm curve while NiFe2O4 and 3, 5 and 7 % ZnO/NiFe2O4 all belong to type IV isotherm curve indicating ZnO as macroporous while NiFe2O4 and different dopant concentration of ZnO/NiFe2O4 are mesoporous. The study shows the complete synthesis of ternary ZnO/NiFe2O4 nanocomposites using green synthesis and sol-gel approach. • Green synthesis of ZnO and NiFe2O4 using leaf extract of Anacardium occidentale • Co-precipitation method at different concentration of ZnO and NiFe2O4 for the synthesis of ZnO/NiFe2O4. • Nanocomposites was characterized using different analytical tools